Calculation of the pressure on the valves of a sluice - Lich, Tran Gia; Luat, Le Kim; Trinh, Han Quoc (Vietnam Journal of Mechanics, 1997)
This paper is devoted to a numerical method for calculating the pressure on the vertical two-dimensional valve basing on Navier-Stokes equations. Numerical solutions at interior points are established by splitting Navie-Stokes unsteady two-dimensional equations into two unsteady one-dimensional equations. An implicit scheme is obtained and the solution for these equations is established by the double sweep method. The values at the boundary points are calculated by the method of characteristics.